Practical antenna design for wireless products - Lau, Henry (Artech House antennas and electromagnetics analysis library., 2019)
This comprehensive resource covers both antenna fundamentals and practical implementation strategies, presenting antenna design with optimum performance in actual products and systems. The book helps readers bridge the gap between electromagnetic theory and its application in the design of practical antennas in real products. Practical implementation strategies in products and systems will be addressed in order to design antennas in the context of actual product environments, including PCB layout, component placement and casing design. Practical design examples on wearable electronic products are presented with a systematic approach to designing antennas for actual products. The book introduces antenna fundamentals to provide the basic concepts and necessary mathematics on electromagnetic analysis, followed by advanced antenna elements. The concept of electromagnetic simulation is presented. The advantages and disadvantages of different numerical methods in antenna modeling are also discussed. Several commercial antenna design and simulation tools are introduced, allowing hands-on practice of antenna modeling and simulation.